Comparing the Effects of Various Implant Abutment Materials on Gingival Fibroblast Attachment In Vitro - Mallikarjun H. Doddamani; Manish Varma; Sumit Bhatt; Veena Raghunath; A. J. Ashmi; Nirupama Vemali (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: Implant abutment materials play a crucial role in influencing peri-implant soft tissue integration and long-term implant success. Gingival fibroblast attachment to abutment surfaces is a key factor in establishing a stable epithelial seal and reducing the risk of peri-implantitis. Materials and Methods: This in vitro study analyzed the attachment of gingival fibroblasts on three commonly used implant abutment materials: titanium (Ti), zirconia (Zr), and polyetheretherketone (PEEK). Disc-shaped specimens (10 mm diameter, 2 mm thickness) of each material were prepared and polished to achieve uniform surface roughness. Gingival fibroblasts were cultured on these specimens in a controlled environment, and cell attachment was assessed using a fluorescence microscopy assay and scanning electron microscopy (SEM). The cell adhesion index (CAI) was calculated after 24 hours, 48 hours, and 72 hours. Data were analyzed using one-way ANOVA and post-hoc Tukey tests with a significance level of P < 0.05. Results: Gingival fibroblast attachment was significantly influenced by the abutment material. Titanium exhibited the highest CAI (mean ± SD: 85 ± 4.5), followed by zirconia (72 ± 3.8) and PEEK (55 ± 4.2) after 72 hours (P < 0.05). SEM analysis revealed well-spread fibroblast morphology on titanium and zirconia surfaces, whereas fibroblasts on PEEK surfaces appeared less spread and more rounded. Conclusion: Titanium and zirconia demonstrate superior gingival fibroblast attachment compared to PEEK, highlighting their potential in promoting soft tissue integration around dental implants. Further studies are needed to validate these findings and explore the clinical implications.